Material properties and design aspects of folding bicycle frame - Maleque, Md. Abdul; Hossain, M. Sayeed; Dyuti, S. (Trans Tech Publications, Switzerland, 2011)
A successful design of folding bicycle should take into account the function, material properties, and fabrication process. There are some other factors that should be considered in anticipating the behavior of materials for folding bicycle. In order to understand the relationship between material properties and design of a folding bicycle and also for the future direction in new materials with new design, a comprehensive study on the design under different conditions are essential. Therefore, a systematic study on the relationship between material properties and design for folding bicycle has been performed. The advantages and disadvantages matrix between conventional bicycle and folding bicycle is presented for better understanding of the materials properties and design. It was found that the materials properties of the folding bicycle frame such as fatigue and tensile strength are the important properties for the better performance of the frame. The relationship between materials properties and design is not straight forward because the behavior of the material in the finished product could be different from that of the raw material. The swing hinge technique could be a better technique in the design for the folding bicycle frame.